World Peace in Western Political Philosophy: A Historical and Analytical Study - Rasho مسرور محمد; Hassan مؤيد بركات (Zanco Journal of Law and Politics گۆڤاری زانكۆ بۆ یاساو رامیاری, 2025)
Abstract This research attempts to understand the issue of world peace as one of the most important global issues, one that has always held a prominent place among thinkers and philosophers throughout history, particularly in Western philosophy. World peace provides a framework for understanding and addressing many of the complex challenges facing the world and forms the basis for communication between effective, competing groups. The concept of world peace should not be interpreted as the opposite of war and military approaches. This doctrine is much broader and encompasses all aspects of peaceful coexistence, not just the prevention of conflicts and disputes. Rather, it aims to build equal and just societies that live in lasting harmony. This research aims to answer the research question about the changes that have occurred in the idea of ​​world peace in the context of the development of Western philosophy, and the intellectual and historical determinants that have shaped this concept. The researcher adopted the historical approach, which enriches this research (qualitative), as well as the analytical approach, given the necessity of researching the history of ideas. We have reached a general conclusion that man is by nature social and cannot live alone. This aspect of social life requires laws and regulations as a constitution for life among people through the formation of a global government. Naturally, through the passage of these wars, conflicts and disputes between national powers to obtain wealth and resources, this shows that achieving world peace is not an easy matter. Rather, it requires efforts exerted by countries to achieve world peace, just as they succeeded in stopping human trafficking that has existed since the ages.